2002
DOI: 10.1126/science.1071329
|View full text |Cite
|
Sign up to set email alerts
|

Reorganization of North Atlantic Marine Copepod Biodiversity and Climate

Abstract: We provide evidence of large-scale changes in the biogeography of calanoid copepod crustaceans in the eastern North Atlantic Ocean and European shelf seas. We demonstrate that strong biogeographical shifts in all copepod assemblages have occurred with a northward extension of more than 10 degrees latitude of warm-water species associated with a decrease in the number of colder-water species. These biogeographical shifts are in agreement with recent changes in the spatial distribution and phenology detected for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

33
661
1
5

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,002 publications
(700 citation statements)
references
References 16 publications
33
661
1
5
Order By: Relevance
“…In the oceans, satellite-derived changes in the area of the subtropical gyres [e.g., Polovina et al, 2008], changes in chlorophyll a [e.g., McClain et al, 2004;Gregg et al, 2005], changes in primary productivity [e.g., Behrenfeld et al, 2006], and shifts in species ranges from in situ measurement [e.g., Beaugrand et al, 2002;Beaugrand and Reid, 2003] are suggested as signs of an altered marine environment.…”
Section: Final Commentsmentioning
confidence: 99%
“…In the oceans, satellite-derived changes in the area of the subtropical gyres [e.g., Polovina et al, 2008], changes in chlorophyll a [e.g., McClain et al, 2004;Gregg et al, 2005], changes in primary productivity [e.g., Behrenfeld et al, 2006], and shifts in species ranges from in situ measurement [e.g., Beaugrand et al, 2002;Beaugrand and Reid, 2003] are suggested as signs of an altered marine environment.…”
Section: Final Commentsmentioning
confidence: 99%
“…Interannual variation in climate and climate change affect marine ecosystems by, e.g., the poleward species range expansions, changes in local species compositions due to physiological intolerance to new conditions (e.g., a shift from marine to brackish or freshwater species with decreasing salinities) and arrival of nonindigenous species, observed across a large number of marine ecosystems (Beaugrand et al 2002, Drinkwater 2002, Daskalov et al 2007, Drinkwater et al 2010. However, more specific changes in climate conditions and, consequently, in the marine environment are often largely determined by the location and general characteristics of the sea (Philippart et al 2011).…”
Section: Future Climate Changementioning
confidence: 99%
“…Cluster analysis of data at sample flow rate of 10 lL/min. The populations analyzed are indicated in Figure 4 (dashed boxes), including the two distinct populations of Alexandrium indicated by g. 1 being adapted for use on unmanned underwater vehicles to track population changes of phytoplankton over time. 22 …”
Section: Discussionmentioning
confidence: 99%
“…1 Pollution and environmental change can cause significant variation in populations of phytoplankton species. Generally, phytoplankton species are collected and later analyzed onshore in marine laboratories.…”
Section: Introductionmentioning
confidence: 99%